The S2–S3 Loop of Kv7.4 Channels Is Essential for Calmodulin Regulation of Channel Activation - Zhuang, Wenhui; Yan, Zhiqiang (Frontiers in Physiology, 2021)
Kv7.4 (KCNQ4) voltage-gated potassium channels control excitability in the inner ear and the central auditory pathway. Mutations in Kv7.4 channels result in inherited progressive deafness in humans. Calmodulin (CaM) is crucial for regulating Kv7 channels, but how CaM affects Kv7 activity has remained unclear. Here, based on electrophysiological recordings, we report that the third EF hand (EF3) of CaM controls the calcium-dependent regulation of Kv7.4 activation and that the S2-S3 loop of Kv7.4 is essential for the regulation mediated by CaM. Overexpression of the mutant CaM1234, which loses the calcium binding ability of all four EF hands, facilitates Kv7.4 activation by accelerating activation kinetics and shifting the voltage dependence of activation leftwards. The single mutant CaM3, which loses the calcium binding ability of the EF3, phenocopies the facilitating effects of CaM1234 on Kv7.4 activation. Kv7.4 channels co-expressed with wild-type CaM show inhibited activation when intracellular calcium levels increase, while Kv7.4 channels co-expressed with CaM1234 or CaM3 are insensitive to calcium. Mutations C156A, C157A, C158V, R159 and R161A, which are located within the Kv7.4 S2-S3 loop, dramatically facilitate activation of Kv7.4 channels co-expressed with wild-type CaM but have no effect on activation of Kv7.4 channels co-expressed with CaM3, indicating that these five mutations decrease the inhibitory effect of Ca2+/CaM. The double mutation C156A/R159A decreases Ca2+/CaM binding and completely abolishes CaM-mediated calcium-dependent regulation of Kv7.4 activation. Taken together, our results provide mechanistic insights into CaM regulation of Kv7.4 activation and highlight the crucial role of the Kv7.4 S2-S3 loop in CaM regulation.